2012
DOI: 10.1097/hjh.0b013e32835850d7
|View full text |Cite
|
Sign up to set email alerts
|

Automated blood pressure measurement in atrial fibrillation

Abstract: There is limited evidence and significant heterogeneity in the studies that validated automated blood pressure monitors in atrial fibrillation. These monitors appear to be accurate in measuring SBP but not DBP. Given that atrial fibrillation is common in the elderly, in whom systolic hypertension is more common and important than diastolic hypertension, automated monitors appear to be appropriate for self-home but not for office measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
2
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 26 publications
1
57
2
6
Order By: Relevance
“…The results of our study are controversial comparing with recent meta-analysis [18], which analysed 566 patients with AF and showed that automated BP findings were higher than manual. Our study, as the meta-analysis, showed that BP measured with oscillometric device was higher in both AF and SR groups.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The results of our study are controversial comparing with recent meta-analysis [18], which analysed 566 patients with AF and showed that automated BP findings were higher than manual. Our study, as the meta-analysis, showed that BP measured with oscillometric device was higher in both AF and SR groups.…”
Section: Discussioncontrasting
confidence: 87%
“…Despite that, recent systematic review and meta–analysis [18] demonstrated that there is limited evidence in studies that validated the automated BP devices in AF. Meta–analysis concluded that oscillometric devices may be suitable for measuring systolic, but not for diastolic BP and may be appropriate for measuring BP at home, but not for office measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were instructed to continue their regular activities during the recording and go to bed no later than 11 pm . The waking period ranged from 8 am to 10 pm and the sleep period from midnight to 6 am  [16]. All individuals were trained to record in a diary the hours during which they were asleep and awake, meals, intake of medications, and symptoms and events that could influence BP during this period.…”
Section: Methodsmentioning
confidence: 99%
“…Однако, если получено достаточное количество адекватных измерений, то их редактиро-вание необязательно, и удалению подлежат только явно неверные показатели. Следует отметить, что неточные данные могут быть получены при выра-женных нарушениях сердечного ритма [70].…”
Section: таблицаunclassified